Prospective comparison of whole-body bone SPECT and sodium 18F-fluoride PET in the detection of bone metastases from breast cancer. Issue 11 (November 2016) - Abikhzer, Gad; Srour, Saher; Fried, Georgeta; Drumea, Karen; Kozlener, Ela; Frenkel, Alex; Israel, Ora; Fogelman, Ignac; Kagna, Olga
Abstract : Objective: The superiority of sodium 18 F-fluoride PET ( 18 F-PET)/computed tomography (CT) over planar and single field-of-view single-photon emission computed tomography (SPECT) bone scintigraphy with 99m Tc-methylene diphosphonate in bone metastases detection has been established. The present study prospectively compares whole-body 99m Tc-methylene diphosphonate SPECT (WB-SPECT) and 18 F-PET performance indices for the detection of bone metastases in breast cancer. Methods: A total of 41 pairs of studies in female breast cancer patients (average age 58 years, range 30–75) were included. Half-time WB-SPECT and 18 F-PET/CT were performed at a 4-day average interval (range 0–36 days), with subsequent fusion of CT to WB-SPECT. Two readers independently interpreted the studies, with differences resolved by consensus. Composite gold standard included the CT component of the 18 F-PET/CT study with follow-up CT, MRI, 18 F-fluoro-deoxyglucose-PET/CT, and bone scans. Results: On patient-based analysis, metastases were diagnosed in 21 patients, with 19 patients detected by WB-SPECT and 21 with 18 F-PET, the latter being the only modality to detect a single metastasis in two patients. The sensitivity of WB-SPECT and 18 F-PET was 90 and 100% ( P =NS), and the specificity were 95 and 85%, respectively ( P =NS). On lesion-based analysis, 284 total sites of increased uptake were found. WB-SPECT detected 171/284 (60%) and 18 F-PET 268/284 (94%) lesions, with good interobserver agreement for WB-SPECT ( κ =0.679) and excellent agreement for 18 F-PET ( κ =0.798). The final analysis classified 204 lesions as benign and 80 as metastases. WB-SPECT identified 121 benign and 50 malignant sites compared with 192 and 76, respectively, for 18 F-PET. WB-SPECT and 18 F-PET had a sensitivity of 63 vs. 95%, P -value of less than 0.001, and a specificity of 97 vs. 96% ( P =NS), respectively, on lesion-based analysis. Conclusion: 18 F-PET had higher sensitivity for the diagnosis of bone metastases from breast cancer compared with WB-SPECT, showing a statistically significant 32% increase on lesion-based analysis.